Deletion of the c2515 and c2516 Genes Affects Iron Uptake and Virulence of APEC O1 Strain E516 - Gao, Qingqing; Li, Xi; Su, Senyan; Yang, Lei; Gao, Song (Frontiers in Veterinary Science, 2021)
Avian pathogenic Escherichia coli (APEC), widely spread among poultry, is well-known to cause colibacillosis in chickens, which results in significant losses in poultry industry. The ability to uptake iron in the extra-intestinal environment is prerequisite for APEC survival. For adaptation to the low-iron environments, the bacteria have evolved multiple iron acquisition systems to ensure optimal iron uptake. However, many components of these iron acquisition pathways are still not clearly known. An in silico analysis of the genome of a septicemic APEC O1 strain E516 identified two putative iron transport genes homologous to the c2515 and c2516 genes from uropathogenic E. coli CFT073. In this study, we constructed the single and double gene deletion mutants, and studied their biological characteristic and pathogenic traits through in vitro and in vivo assays. Reverse transcriptase PCR (RT-PCR) analyses demonstrated that the mutations destroying the reading frame of the target genes abolished their transcription. Deletion of the single or double genes of c2515 and c2516 in APEC E516 weakened its ability to produce siderophore. Consistently, the mutants exhibited growth defect under iron-depleted conditions and the intracellular iron levels in the mutants were decreased in comparison with that of the wild-type (WT). Cell infection assays showed that the iron uptake defective mutants were more easily eliminated by the macrophage. Inactivation of the c2515 and c2516 genes affected bacterial colonization of chicken tissues, as well as the 50% lethal dose levels compared with the WT strain. Moreover, the expression levels of several iron uptake-related genes were significantly decreased in the double-deletion mutant. In total, the c2515 and c2516 may involve in siderophore-mediated iron uptake and participate in the pathogenesis of APEC O1 strain E516.